Deterministic and stochastic topics in computational finance - Calin, Ovidiu (World Scientific, 2017)
What distinguishes this book from other texts on mathematical finance is the use of both probabilistic and PDEs tools to price derivatives for both constant and stochastic volatility models, by which the reader has the advantage of computing explicitly a large number of prices for European, American and Asian derivatives. The prerequisites are an introductory course in stochastic calculus, as well as the usual calculus sequence. The book is addressed to undergraduate and graduate students in Masters of Finance programs as well as to those who wish to become more efficient in their practical applications.